Isolation and identification of a novel goose-origin reovirus GD218 and its pathogenicity experiments - Li, Yuze; Yang, Huihu; Lu, Yongkun; Yin, Zhenghao; Xu, Hang; Mei, Kun; Huang, Shujian (Frontiers in Veterinary Science, 2024)
Since 2020, a novel goose-derived reovirus, characterized by goose hemorrhagic hepatitis, has emerged in the goose breeding industry of Guangdong province, China, leading to significant economic losses in the poultry sector. To study the genetic variation of novel goose reovirus (NGRV) in Guangdong province, this experiment utilized goose embryonic fibroblast cells for virus isolation. RT-PCR was conducted to identify, amplify, clone, and sequence the complete genome of the NGRV isolated from Zhaoqing. The genomic sequences were compared with reference strains to construct a phylogenetic tree. Moreover, animal pathogenicity, excretion patterns, and pathological sections were examined. The results showed that liver and spleen samples from geese suspected of NGRV infection were used for isolation, resulting in the identification of a reovirus presumed to originate from geese, designated as GD218. In terms of genomic structure and sequence homology, GD218 closely resembles the novel duck reovirus, differing significantly from earlier isolated NDRV strains (J18, NP03, SD12, etc.) in genetic composition (nt: 80.6–97.9%, aa: 94.3–98.9%). However, it is similar to strains isolated after 2018, such as XT18, SY, QR, YL, LY20, etc. (nt: 95.3–98.9%, aa: 98.6–99.7%). Therefore, based on phylogenetic analysis, GD218 is hypothesized to be a novel type of goose-origin reovirus homologous to the novel duck reovirus.